Download presentation

Presentation is loading. Please wait.

Published byRoss Flowers Modified over 9 years ago

1
EXAMPLE 1 Solve a linear-quadratic system by graphing Solve the system using a graphing calculator. y 2 – 7x + 3 = 0 Equation 1 2x – y = 3 Equation 2 SOLUTION STEP 1 Solve each equation for y. y 2 – 7x + 3 = 0 y 2 = 7x – 3 y = + 7x – 3 Equation 1 2x – y = 3 –y = –2x + 3 y = 2x – 3 Equation 2

2
EXAMPLE 1 Solve a linear-quadratic system by graphing STEP 2 Graph the equations y = y = and y = 2x – 3 7x – 3, – Use the calculator’s intersect feature to find the coordinates of the intersection points. The graphs of and y = 2x – 3 intersect at (0.75, –1.5). The graphs of and y = 2x – 3 intersect at (4, 5). y = – 7x – 3, y = 7x – 3,

3
EXAMPLE 1 Solve a linear-quadratic system by graphing ANSWER The solutions are (0.75, –1.5) and (4, 5). Check the solutions by substituting the coordinates of the points into each of the original equations.

4
EXAMPLE 2 Solve a linear-quadratic system by substitution Solve the system using substitution. x 2 + y 2 = 10 Equation 1 y = –3x + 10 Equation 2 SOLUTION Substitute –3x + 10 for y in Equation 1 and solve for x. x 2 + y 2 = 10 x 2 + (–3x + 10) 2 = 10 x 2 + 9x 2 – 60x + 100 = 10 10x 2 – 60x + 90 = 0 x 2 – 6x + 9 = 0 (x – 3) 2 = 0 x = 3 Equation 1 Substitute for y. Expand the power. Combine like terms. Divide each side by 10. Perfect square trinomial Zero product property

5
EXAMPLE 2 Solve a linear-quadratic system by substitution y = – 3(3) + 10 = 1 To find the y -coordinate of the solution, substitute x = 3 in Equation 2. ANSWER The solution is (3, 1). CHECK You can check the solution by graphing the equations in the system. You can see from the graph shown that the line and the circle intersect only at the point (3, 1).

6
GUIDED PRACTICE for Examples 1 and 2 1. x 2 + y 2 = 13 y = x – 1 (3,2), (–2, –3) 2. x 2 + 8y 2 – 4 = 0 y = 2x + 7 no solutions 3. y 2 + 6x – 1 = 0 y = –0.4x + 2.6 (–1.57, 3.23), (–22.9, 11.8). ANSWER

7
GUIDED PRACTICE for Examples 1 and 2 4. y = 0.5x – 3 x 2 + 4y 2 – 4 = 0 no solution. (3, –4), (–3, 2) ANSWER 5. y 2 – 2x – 10 = 0 y = x 1 – – ANSWER 6. y = 4x – 8 9x 2 – y 2 – 36 = 0 (2, 0), (, ) ANSWER 7 50144 7

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google